Pregnancy outcome after antepartum diagnosis of oligohydramnios at or beyond thirty seven completed weeks in rural India - Gupta, Kumud Ashok; Hasabe, Rakesh Appasaheb; Aggarwal, Sumedha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Amniotic fluid volume abnormalities may reflect a problem with fluid production or its circulation, such as underlying fetal or placental pathology. These volume extremes may be associated with increased risks for adverse pregnancy outcome. Some studies show that amniotic fluid index is a poor predictor of adverse outcome and some authors have not confirmed the association of adverse perinatal outcome with oligo-hydramnios. Thus this study is conducted to find out the value of oligohydramnios in perinatal outcome and maternal outcome in pregnancies beyond 37 completed weeks. Methods: This study was done at department of Obstetrics and Gynaecology, NIMS hospital, Jaipur, Rajasthan, India, from January 2013 to January 2015 for a period of 24 months. Our analysis included a total of 200 antenatal women; both booked and unbooked were included in this study. In this study 100 women with AFI <5 cm were allotted into the study group and another 100 women with normal AFI were included into the control group. Labour was either spontaneous or induced in both study and control group . During labour intermittent auscultation of fetal heart rate was done to detect any signs of fetal distress. Artificial rupture of membranes was done in active phase of labour to notice the grade of liquor and progress of labour was monitored on a partogram. Mode of delivery and intrapartum complications were noted. At birth neonate was assessed using 5 minute APGAR score , birth weight was recorded and neonate who were admitted into NICU were followed until discharge. Results: Oligohydramnios i.e., AFI <5 cm measured by ultrasonography in term pregnancies is associated with adverse perinatal outcome. The risks of meconium staining of liquor, intrapartum fetal distress,operative delivery and perinatal mortality are significantly higher in patients with AFI <5 cm , compared to those with normal AFI. Conclusions: Determination of AFI can be used as an adjunct to other fetal surveillance methods. It helps to identify those infants at risk of poor perinatal outcome. Determination of AFI is a valuable screening test for predicting fetal distress in labour requiring cesarean section.